Sistem Pendukung Keputusan Pemilihan Ketua Organisasi BKM (Badan Keswadayaan Masyarakat) Menerapkan Metode MOORA - Dira amalia; Ade Irma Agustina Lubis; Alwin Fau (Journal of Informatics, Electrical and Electronics Engineering, 2023)
The Organization of the Non-Governmental Organization (BKM) is an institution consisting of a group of citizens/communities who are natives of the kelurahan/village, an organization which is a form or a place for people to gather between one or more people who work together to achieve goals. a goal. What can determine the success or failure of an organization can be seen from its human resources. The Community Non-Governmental Organization (BKM) of the Al-Hidayah Mosque, which is located in the Marindal 1 Pasar 3 area, Deli Serdang Regency, North Sumatra. Where the non-governmental organization (BKM) has advantages in maintaining and caring for the Al-Hidayah Marindal 1 Pasar 3 mosque to keep it looking neat and clean, this study aims to build a decision support system (DSS). Which has a function as a tool for determining decision making in the process of selecting the Chairperson (BKM) of the Al-Hidayah Marindal 1 Pasar 3 mosque. This is also done with great attention to several aspects which are an important strategy that will be considered in the election of the chairman (BKM) of the mosque. Al-Hidayah marindal 1 market 3 absolutely and very much needed. The Moora method is one of the Multi-Criteria decision making (MCMD). A method that requires statistical procedures for the selection of the best given alternative. This method also produces a very suitable alternative by considering something good and profitable. The highest ranking result from this research is alternative A4 (Rudi Hartono